Pengaruh ketersediaan dana kontan terhadap pengadaan dan penggunaan obat tingkat puskesmas = The impact of the availability of the fund in cash on the supply and the use of the drugs at the puskesmas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: The economic crisis in Indonesia since mid 1997 resulted in negative impact on health status of people, especially that of poor families. The government of the Republic of Indonesia made a policy on social safety net (JPS-BK) in which a certain number of cash funds are directly managed by Puskesmas (Community Health Center). A part of the fund was used by the clinics to make the drugs necessary would make the management of the drugs at the Puskesmas level more irrational. Therefore, a study needs to conduct to investigating the use of the fund in cash at the level. Objective: The objective of the study was to investigate the impact of cash fund availability on drug supply and utilization at the Puskesmas. The particular objective was to compare the pattern of drug supply and utilization before and when the cash fund has been available in the Puskesmas to purchase brand name and non essential drugs and the impact cash fund availability on drugs purchase, the use of non essential drugs, polypharmacy, generic prescribing, drug cost in each prescription, and the use of antibiotic and injection. Method: The study was designed as quasi-experiment involving 24 Puskesmas in 4 regencies, two of which were model regencies in regional autonomy and the other two were not. The pattern in drug supply was measured retrospectively before the availability of the JPS-BK fund in the Puskesmas in 1996/1997 and on the availability of it in 1998/1999. A survey on prescription writing was conducted to investigate the use of the drugs in the Puskesmas in 1996/1997 and 1998/1999 with a total number 2160 prescription as samples. The data was analyzed using t-test and chi-square methods. Result: The result of the study showed that availability of the JPS-BK fund significantly increased the drug cost in each prescription (P